Low serum albumin – another prognostic marker? - Arantes, C (2015)
Introduction: Population-based studies have suggested an association between low serum albumin levels and coronary atherosclerosis and heart failure. The role of albumin in the context of acute coronary syndromes (ACS) remains unclear, however, seems to associate with an adverse prognosis. Aim: The aim of the present study was to determine whether low serum albumin levels are associated with development of heart failure in ACS. Methods: Study of patients consecutively admitted for ACS in a Coronary Unit over 6 months. Patients with infectious complications were excluded. Results: One hundred sixty-eight patients were eligible for analysis. Males were predominant (81.5%) and the mean age was 61.7±13.4 years old. Low serum albumin levels (serum albumin <3.5g/dl) were present in 44.6%. No significant differences were observed regarding demographic characteristics, except higher mean age (p <0.001) and a higher prevalence of hypertension (p = 0.04) in the hypoalbuminemia group. This group had lower values of hemoglobin (p<0.001) and higher levels of pro-BNP (p=0.018) and C Reactive Protein (p<0.001). In univariate analysis, hypoalbuminemia was associated with a higher prevalence of heart failure (p=0.015, OR 2.45 CI95% 1.17-5.10) and the use of intra-aortic balloon (p = 0.005) during hospitalization. There were no statistically significant differences in the use of ionotropic drugs and invasive ventilation as well as in-hospital mortality. At follow-up at 6 months showed a positive association between hypoalbuminemia and mortality (p <0.05). Conclusions: The hypoalbuminemia was associated with an increased risk of heart failure during hospitalization and death at 6 months. Although the etiology of hypoalbuminemia remain unclear, albumin assay may be useful in risk stratification of acute coronary syndromes.